'Live and local'?: The significance of digital media for writers' festivals. (February 2017) - Murray, Simone; Weber, Millicent
Literary festivals throughout the English-speaking world have been enthusiastic adopters of digital technology: uploading podcasts of author talks, posting videos of panel sessions to video-sharing sites such as YouTube, inviting guest bloggers to comment on proceedings and encouraging live-tweeting as a means of reinforcing audience members' participatory agency. Such innovations serve to expand festivals' reach to encompass dispersed audiences and, moreover, increase the longevity of previously transient events. They hence provide evidence to justify writers' festivals' claims on public funding as well as to delineate vibrant online and offline bookish communities of interest. However, wholesale uptake of digital technology destabilizes some previous givens of the literary festival as they have coalesced since the phenomenon's 1980s efflorescence. The concept of authorship undergoes profound changes in a climate of online performativity, constant availability to readerships and digitally diminished 'aura'. Equally, previously passive audiences are reconceptualized as amateur critics, co-publicists and even co-publishers in the case of crowdsourced subscription publishing. Festival programming may be sampled live or archived, and audiences are only partially tethered to a particular geographical location – a disarticulation taken to another level by emerging online-only writers' festivals such as the #TwitterFiction Festival and the Digital Writers' Festival. What are the implications of these shifts for our conceptualization of 21st-century literary community? This article seeks to address this question by proposing a theoretical framework for examining the digital/literary festival interface, analyzing a wide range of terrestrial and online-only festivals and underpinning this analysis with empirical audience interviewing conducted at multiple Australian and UK writers' festivals and book towns. In bringing together these strands, the article presents a detailed picture of an important and currently underexplored dimension of the public encounter with literature at a moment of profound digital change.